Decision-making between hybrid renewable energy configurations and grid extension in rural areas for different climate zones. (1st January 2023) - Demirci, Alpaslan; Öztürk, Zafer; Tercan, Said Mirza
Abstract: The growing population and technological developments have led to irregular houses and especially industrial facilities in developing cities. Furthermore, due to social and economic factors and the increasing massive migrations, undeveloped rural projects make irregular settlements worse. Thus, the expensiveness caused by the deterioration of the supply-demand balance makes establishment or production capacity increase of industrial facilities difficult. In this study, supplying the industrial urban facilities' demand with only grid or on-grid/off-grid HPS scenarios were investigated considering expanding and relocation outside the city. Twelve industrial cities in Turkey with various climates have been evaluated using Homer ® Pro, considering the effects of RES potential on the techno-economic parameters. The results showed that the RES potentials changed break-even distance for grid extension between 0 and 25 km. Furthermore, it has been determined that the change in the discount rate and the grid extension costs, which vary depending on the regional geographical conditions, seriously manipulate break-even distance. Particularly, it can be extended up to 55 km depending on RES potentials and grid extension capital cost. In contrast, high RES potential make unnecessary grid extension, especially where the discount rate was less than 4%. Finally, sensitivity analyses are also presented in detail. Highlights: Decision-making between the hybrid power systems and grid extension is conducted. A circular break-even distance map offers an optimum HPS depending on the DR. The break-even distance is 35 km for the only grid and 55 km for integrated HPS. Increases in DR can lead to CO2 emissions rising 1.87–3.54 times. The renewable fraction rises from 85 to 97%, causing an apparent increase in NPC.